Self-Reported and Objectively Measured Physical Activity of Elderly Women in Podgorica - Katarina Dragutunovic (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this paper was to determine the physical activity of elderly women and to analyze the age-related decline in physical activity in older women. The survey was conducted in Podgorica, on a sample of 100 participants. For the age-group comparisons we subdivided the sample younger group (77 participants aged 50-59 years) and older group (23 participants aged 60-69 years). In this research, the long form of the IPAQ questionnaire for self-evaluation was used containing four types questions of Physical Activity: work-related, transportation, housework/gardening and leisure-time activities. The three levels of physical activity suggested for classifying the populations are low, moderate, and high. If one takes into account the type of physical activity, the results indicate that there is a statistically significant difference between the younger and older elderly group of respondents in variables: total walking and overall stressful activities. Our research has shown that, overall, the group respondents from 50 to 59 years is more active than the group from 60 to 69 years of respondents. It has been determined that women of the third age are physically active and there is a statistically significant difference between the two sub-samples when it comes to overall physical activity, or rather that it decreases with age.